Pollutants of Emerging Concern in Treated Urban Wastewater in Acapulco Guerrero, Mexico - Martinez-Organiz A.; Mendoza-Ramos J. E.; Herrera-Navarrete R. (Research Advances in Environment, Geography and Earth Science Vol. 6, 2024)
Treated urban wastewater is an important source of emerging contaminants (EC), since conventional wastewater treatment plants (WWTP) are not designed to efficiently remove these contaminants, facilitating their entry into the aquatic environment through the effluents. This study focused on identifying EC in the influent and effluent of a conventional urban WWTP. Analytical methods such as high-performance mass spectrometry (LC-HRMS) and high-performance liquid chromatography coupled with tandem mass spectrometry (HPLC-MS/MS) were used to analyze samples, using a non-target compound approach that seeks to identify all compounds present in the samples without prior selection. The results revealed the presence of a variety of ECs, including antibiotics such as sulfonamides (sulfamethoxazole) and fluoroquinolones (ciprofloxacin and ofloxacin), drugs such as carbamazepine, oxcarbazepine, metoprolol, alprenolol, lidocaine and metaxolone, as well as pesticides, predominantly insecticides and fungicides in the effluent. These contaminants can have toxic effects and bioaccumulate in marine organisms, threatening biodiversity and affecting human health by integrating into the food web. The importance of carrying out continuous monitoring studies of EC in aquatic ecosystems that receive treated water from WWTPs is emphasized, in order to identify priority sources of EC according to their toxicity. This knowledge would allow the treatment technologies used to be adapted to mitigate impacts on human health and the ecosystem. Implementing effective management strategies that address the presence of ECs in treated wastewater is essential to preserve water quality and the health of aquatic ecosystems and human communities.